Coronary computed tomography angiography following robotic coronary artery bypass grafting surgery: Systematic approach to image analysis and practical considerations. (July 2021) - Pasha, Ahmed Khurshid; Lee, Justin Z.; Poston, Robert S.; Abidov, Aiden
Abstract: Standard open chest Coronary Artery Bypass Grafting (CABG) has evolved over last couple of decades. With advancement in minimally invasive procedures, Robotic CABG (RCABG) is still in its evolution phase. There is dearth of experienced surgeons in this complicated field and lack of data to verify it clinical safety. in this review, we intend to describe the utility of Cardiac Computed Tomography Angiography (CCTA) in assessment of graft anatomy and quality, grafting strategy, distal graft anastomosis site evaluation and detection of complications associated with RCABG. CCTA appears to provide valuable information regarding the visualization of grafts, target coronary arteries and other cardiac and non-cardiac structures. Highlights: Surgical morbidity and mortality is improved in robotic CABG given small incisions and preserved integrity of sternum and the chest wall. CCTA is helpful in evaluating graft anatomy, assessing graft origin and distal anastomosis and detection of complications associated with the robotic CABG. CCTA also provides important diagnostic information regarding the native coronary arteries and other cardiac and non-cardiac structures.